On the Toxicity of Therapeutically Used Nanoparticles: An Overview. (6th January 2009) - El-Ansary, A.; Al-Daihan, S.
Abstract : Human beings have been exposed to airborne nanosized particles throughout their evolutionary stages, and such exposures have increased dramatically over the last century. The rapidly developing field of nanotechnology will result in new sources of this exposure, through inhalation, ingestion, and injection. Although nanomaterials are currently being widely used in modern technology, there is a serious lack of information concerning the human health and environmental implications of manufactured nanomaterials. Since these are relatively new particles, it is necessary to investigate their toxicological behavior. The objective of this review was to trace the cellular response to nanosized particle exposure. Therapeutic application of selected nanoparticles together with their range of toxic doses was also reviewed. Effect of therapeutically used nanoparticles on cell membrane, mitochondrial function, prooxidant/antioxidant status, enzyme leakage, DNA, and other biochemical endpoints was elucidated. This paper highlights the need for caution during the use and disposal of such manufactured nanomaterials to prevent unintended environmental impacts.